2021
DOI: 10.1371/journal.pmed.1003602
|View full text |Cite
|
Sign up to set email alerts
|

Parenting interventions to promote early child development in the first three years of life: A global systematic review and meta-analysis

Abstract: Background Parents are the primary caregivers of young children. Responsive parent–child relationships and parental support for learning during the earliest years of life are crucial for promoting early child development (ECD). We conducted a global systematic review and meta-analysis to evaluate the effectiveness of parenting interventions on ECD and parenting outcomes. Methods and findings We searched MEDLINE, Embase, PsycINFO, CINAHL, Web of Science, and Global Health Library for peer-reviewed, published … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
309
5
19

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 354 publications
(464 citation statements)
references
References 158 publications
19
309
5
19
Order By: Relevance
“… 5 In contrast, stimulation interventions (n=21) were found to be more beneficial for cognitive ( d =0.43) and language ( d =0.47) development than nutrition interventions (n=18, d =0.09) in children younger than 2 years. 6 Furthermore, a recent review by Jeong et al 7 found that stimulation-based interventions have considerably larger effects on cognitive (standardised mean difference [SMD]=0.41), motor (SMD=0.26), language (SMD=0.35) and socioemotional (SMD=0.24) development of children under 3 years in LMICs.…”
Section: Introductionmentioning
confidence: 99%
“… 5 In contrast, stimulation interventions (n=21) were found to be more beneficial for cognitive ( d =0.43) and language ( d =0.47) development than nutrition interventions (n=18, d =0.09) in children younger than 2 years. 6 Furthermore, a recent review by Jeong et al 7 found that stimulation-based interventions have considerably larger effects on cognitive (standardised mean difference [SMD]=0.41), motor (SMD=0.26), language (SMD=0.35) and socioemotional (SMD=0.24) development of children under 3 years in LMICs.…”
Section: Introductionmentioning
confidence: 99%
“…19 More recently, a systematic review of parenting interventions delivered during the first 3 years of children's lives included nine (of 102) studies in six African countries (of 33 countries globally). 20 The African programmes ranged from an adaptation of the 2-year Reach Up programme in rural Madagascar, 21 which was not found to change ECD outcomes, to an 8-week book-sharing training programme for caregivers living in a peri-urban settlement in South Africa, 22 which was shown to impact children's language development and sustained attention. In rural Uganda, a programme similar to the RPP in design was found to increase children's cognitive and language scores in the programme group compared with control.…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…1 4 14 In the recent systematic review of parenting programmes for children 0-3 years, a greater effect on cognitive development was found in LMICs compared with HICs. 20 An earlier review of a wide range of interventions in LMICs that targeted learning outcomes for children 0-8 years found that child-focused educational interventions had larger effects on the cognitive development of children from low-income compared with high-income families. 56 Preserving the status quo perpetuates and ultimately widens the inequality gap in child health and development between the educated rich and the uneducated poor, 54 raising ethical concerns of inaction when action is possible.…”
Section: Justicementioning
confidence: 99%
“…• Parent education on responsive caregiving in the first 3-years of life and parent strategies for home-based activities that can assist development across domains • This is with the understanding that early nurturing home environments protect young children against effects of early adversities 23 and interventions in the first 3 years of life improved early child cognitive, language, motor, socioemotional development, and attachment and reduced behavioural problems 24 • Strategies for baby-bonding and attachment that can be executed in the home setting, for example, infant massage. 25 • Including content on caregiver burden, maternal mental health and how to maintain the quality of life for caregivers of children with DD • Parent workshops on how to make and use low-cost stimulation toys or apparatus for developmental stimulation in the home • Strategies on how to integrate developmental stimulation into everyday tasks, routines and activities Early evaluation and intervention include not only management and treatment for the individual child but also provision of appropriate family and community-based support mechanisms 18 Parents of children with DD may be more likely to have lowquality parent-child interactions because of increased difficulty in parenting this population 19 Understanding what families' needs are and how families use and integrate strategies within the context of their daily lives provides practitioners with insights needed to support families' resiliency in promoting their children's participation 20 Parents could be intervention agents to facilitate their children's language and social communication outcomes 21 with parent-implemented interventions at time proving more effective than clinician-directed service provision 22 CHWs, community healthcare workers; DD, developmental delays; PHC, primary health care; EI, early intervention; MDT, multidisciplinary team; LMIC, low to middle-income country/ies.…”
Section: Caregiver or Parent Educationmentioning
confidence: 99%
“…This is with the understanding that early nurturing home environments protect young children against effects of early adversities 23 and interventions in the first 3 years of life improved early child cognitive, language, motor, socioemotional development, and attachment and reduced behavioural problems 24 …”
Section: Promoting Early Intervention At Primary Healthcare Levelmentioning
confidence: 99%